Histological study of human dental alveols treated with xeno-graft in implantology - Jammal, María Victoria (2021)
Dental implants are the treatment to replace missing teeth. The success of this therapy is achieved if the existing bone is sufficient to surround and stabilize the implant. While, when it is not, the application of a bone graft or substitute is essential. The most widely used is the autograft or autologous bone due to its biocompatibility. However, the market offers other variants, such as bovine bone xenografts that are used in daily practice. The objective of this study was to evaluate 3 bovine xenografts (BIOSS, TIOSS and SYNERGY) applied to alveoli after human extraction during prosthetic rehabilitation with implants. Bone tissue samples were treated with: Group 1, TIOSS; Group 2, BIOSS; Group 3, Synergy; Group 4, without substitute (clot). Histopathological studies were carried out. The interpretation of bone biopsies was made following ISO Standards 10993-6 Year 2007: A- Biocompatibility: inflammation, foreign body reaction (FBR), abscesses, necrosis, fibrosis, macrophages. B- Bone neoformation: type of bone, presence/absence of particles, and rate of resorption. Histometric and statistical studies. The histological results obtained at 4 months were: (A) Biocompatibility: Group 1 – TIOSS: moderate chronic inflammation. Presence of FBR, abundant lymphocytes. Group 2 and 3 – BIOSS and Synergy similar behavior with a few chronic inflammation and absence of FBR. Group 4 (clot) – absence of FBR. None of the cases presented necrosis and/or abscesses. (B Bone neoformation: Group 1 – TIOSS: amorphous particles surrounded by numerous congestive vessels and predominantly lax connective tissue and newly composed bone (38%). Group 2 and 3 – BIOSS and Synergy: particles surrounded by fibrovascularized tissue and newly composed bone (47% BIOSS and 49% Synergy) with abundant fatty bone marrow. Group 4 (clot) – laminar bone type (45%). New bone percentages did not show statistically significant differences (P = 0.2). The reabsorption rate of the particles was low in the 3 substitutes evaluated by their persistence at 4 months post placement in the alveolus. From the results obtained, we conclude that BIOSS and Synergy had better biological behavior due to the absence of FBR. All three stimulated bone neoformation. The low reabsorption rate prevented alveolar bone atrophy after extraction and maintained the dimensions of the receptor zone; beneficial events for the stability of the implant and its osseo integration.